Karakteristik Fisikokimia Biochar Ampas Kopi dengan Perbedaan Perlakuan Suhu dan Waktu Pirolisis - Mohamad Mukhlis Sutiyoso; Razhika Faradila; Tantalu Lorine (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2025)
Indonesia's ever-increasing energy demand is driving the search for environmentally friendly and sustainable alternative energy sources. One potential renewable energy source is biomass, including abundant but underutilized coffee grounds. This study aimed to examine the effect of varying pyrolysis temperature and time on the physicochemical characteristics of biochar produced from coffee grounds. The pyrolysis process was carried out at varying temperatures of 500°C, 600°C, and 700°C with retention times of 30 minutes, 90 minutes, and 150 minutes. Biochar analysis included moisture content, ash content, volatile matter content, fixed carbon content, pore size, and pH. The results showed that increasing pyrolysis temperature and time significantly affected the physical and chemical properties of biochar. Higher temperatures produced biochar with higher fixed carbon content and calorific value, but decreased yield and increased ash content. Longer pyrolysis times also contributed to increased carbon stability, although they also decreased volatile matter content. Optimum conditions were achieved at a temperature of 500°C for 90 minutes, producing biochar with the best characteristics as an alternative fuel, low moisture content, low ash content, and a pore size of 20 µm,pH 7,63 This research confirms the high potential of coffee grounds to be processed into high-quality biochar through proper control of pyrolysis parameters. These findings can support sustainable coffee waste management strategies while providing environmentally friendly alternative energy Abstrak Beberapa kondisi menjadi perhatian atas permintaan energi yang terus meningkat sehingga sumber energi alternatif yang ramah lingkungan dan berkelanjutan mengalami permintaan yang meningkat. Salah satu sumber energi terbarukan potensial adalah biomassa, termasuk ampas kopi yang melimpah namun belum dimanfaatkan optimal. Penelitian ini bertujuan mengkaji pengaruh variasi suhu dan waktu pirolisis terhadap karakteristik fisikokimia biochar ampas kopi. Proses pirolisis dilakukan pada suhu 500 °C, 600 °C, dan 700 °C dengan waktu tinggal 30, 90, dan 150 menit. Analisis biochar meliputi kadar air, kadar abu, zat terbang, karbon tetap, nilai kalor, pH, serta morfologi pori. Hasil penelitian menunjukkan bahwa peningkatan suhu dan waktu pirolisis secara signifikan memengaruhi sifat biochar. Suhu tinggi menghasilkan biochar dengan kadar air dan zat terbang rendah, pH alkalis, serta struktur pori yang lebih berkembang, meskipun diikuti dengan peningkatan kadar abu. Kondisi optimum diperoleh pada suhu 700 °C selama 150 menit dengan karakteristik unggul: kadar air 1,48%, kadar abu 23.50%, karbon tetap 51.26%, dan pH 11.30. Temuan ini mengonfirmasi potensi ampas kopi sebagai bahan baku biochar berkualitas tinggi yang mendukung strategi pengelolaan limbah berkelanjutan sekaligus menyediakan sumber energi alternatif ramah lingkungan.